Green Economy Index Development as a Measurement Instrument for Green Economy Transition in Bogor Regency - Aidha Zulaika; Tjahjo Tri Hartono; Yuggo Afrianto; Immas Nurhayati; Ratna Pratini; Tazkialaras (Universitas Ibn Khaldun Bogor, 2025)
This study develops and implements the Green Economy Index (GEI) as an instrument for measuring green economy transition in Bogor Regency. Using a composite index methodology adopted from OECD and UNDP best practices, the GEI integrates 15 indicators across three pillars: economic (6 indicators), social (4 indicators), and environmental (5 indicators). Data were collected from official government publications (BPS, KLHK) for the period 2020-2024. The index was constructed using min-max normalization and geometric mean aggregation. Model validation through backtesting showed a Mean Absolute Percentage Error (MAPE) of 5.10%, classified as